Management of the Rookie Basketball Academy Development in Klaten City 2025 - Alfian Agung Putranto; Rumini (Universitas Negeri Semarang, 2025)
This study aims to determine and describe the coaching management implemented at the Rookie Basketball Academy in Klaten City in 2025. This study is motivated by the importance of structured coaching management in non-formal basketball academies such as the Rookie Academy in Klaten, in order to overcome the challenges of coaching young athletes and support the improvement of sports achievements professionally. This study uses a qualitative method with a descriptive approach. Data collection techniques through observation, in-depth interviews, and documentation. The main instruments used in this study were interview guidelines, observation sheets and documentation sheets. The subjects in this study were administrators consisting of 1 coach, 1 assistant coach and 15 athletes who are members of the Rookie Basketball Academy. The selection of subjects was done purposively. The results of the study show that coaching management at the Rookie Basketball Academy has implemented the functions of planning, organizing, implementing, and supervising with a fairly good commitment. The implementation of training is carried out routinely and has received positive responses from athletes, although the level of attendance is still fluctuating and the training methods are considered less varied. This finding emphasizes the need to strengthen the documentation aspect, data-based evaluation system, and organizational structuring in order to improve the effectiveness of coaching as a whole. Suggestions that can be given to the Rookie Basketball Academy are that it needs to develop a more structured documentation system related to training planning, attendance, and periodic evaluation of athlete development.